Phenotypic characteristics of East African goats in Kajiado and Baringo districts of Kenya - Indetia, D.; Karimi, S.; Wandera, F.; Lebbie, S.H.B.; Okeyo Mwai, Ally (Kenya Agricultural Research Institute, 1999)
Survival of indigenous livestock of Kenya could be threatened by existing programmes that promote exotic breed importation or indiscriminate crossbreeding. Thus, there is a need for proper description of existing genetic resources with an aim of determining their Development, utilisation and conservation. Phenotypic characteristics of 263 East African Goats were recorded in Baringo and Kajiado Districts. The goats were categorised by dentition (milk, young, mature) and liveweight. Linear measurements recorded were heart girth, withers height, back, tail, ear, toggle and horn lengths. In both regions, 2 percent of the goats had toggles. Polledness was observed in 6 percent and 16 percent for goats in Baringo and Kajiado, respectively. Brown coat colour was observed in 32 percent and 52 percent of the flock while black skin colour was found in 78 percent and 36 percent of the goats in Baringo and kajiado, respectively. Live weight for each dentition category was higher (P < 0.05) in Kajiado than Baringo. Linear measurements showed similar trends. Milk teeth goats in Kajiado had correlations of 0.92, 0.69 and 0.73 while those of Baringo had 0.94, 0.77 and 0.82 (P < 0.05) for weight with heart girth, withers height and back length, respectively. In mature goats the respective correlations were 0.41, 0.12 and 0.12 in Baringo and 0.81, 0.39 and 0.11, in Kajiado. A stepwise regression of body weight on linear measurements for young goats in Baringo and Kajiado included heart girth and withers height with an R2; of 0.61 while back length was also included for Kajiado with an R2 of 0.89. Only heart girth was included for mature goats with an R2 of 0.18 and 0.66 for Baringo and Kajiado, respectively. Proportions of weight to girth were 3.5, 2.9, 2.4 for young, growing and mature goats, respectively. Similar trends were exhibited for weight with other linear measurements. Girth to withers proportion was 0.93, 0.94 and 0.91 for young, growing and mature goats respectively. Linear measurements are good predictors of liveweight and therefore indicators for performance. The regional differences observed suggest that East African goats can be divided into various types or populations, based on specific phenotypic characteristics.